Efeitos da adição de surfactantes na interação água-óleo de formações características do pré-sal brasileiro - Dantas, Ana Paula Tertuliano (2018)
This research aimed to study the suitability of commercial surfactants in enhanced oil recovery, with the purpose of maximizing the oil production of Brazilian pre-salt carbonate reservoirs. For this, analysis of fluid-fluid interaction between different types of surfactant solutions with oil and representative brine from Pre-Salt fields. The Critical Micelar Concentration (CMC) of the surfactants were determined to measure the concentration to be used, followed by determination of chemical and thermal stability of the surfactants in formation water and the influence of its salinity on the behavior of phases, through a salinity scan. Finally, after determining the suitability of the surfactants at reservoir conditions, the interfacial tension of the system containing brine, surfactant and oil extracted from a Pre-Salt field was studied. The results showed the amphoteric surfactants as the most stable at the salinity and temperature conditions to which they have been tested, with optimal application salinities ranging between 60,000 ppm and 150,000 ppm. The results for interfacial tension were aligned with mentioned results, indicating reduction of one order of magnitude with surfactant addition.